Progress and challenges for abiotic stress proteomics of crop plants - Barkla, B. J.; Vera-Estrella, R.; Pantoja, O.
Plants are continually challenged to recognize and respond to adverse changes in their environment to avoid detrimental effects on growth and development. Understanding the mechanisms that crop plants employ to resist and tolerate abiotic stress is of considerable interest for designing agriculture breeding strategies to ensure sustainable productivity. The application of proteomics technologies to advance our knowledge in crop plant abiotic stress tolerance has increased dramatically in the past few years as evidenced by the large amount of publications in this area. This is attributed to advances in various technology platforms associated with MS-based techniques as well as the accessibility of proteomics units to a wider plant research community. This review summarizes the work which has been reported for major crop plants and evaluates the findings in context of the approaches that are widely employed with the aim to encourage broadening the strategies used to increase coverage of the proteome.
Keywords: ABIOTIC STRESS; CROP PLANTS; MASS SPECTROMETRY; PLANT PROTEOMICS